A fajtaminősítés kérdése gabonafélékben toxikus gombákkal szemben. A termés nem minden - Mesterházy, Ákos; Szabó, Balázs; Berényi, Attila; Meszlényi, Tamás; Tóth, Beáta (GEORGIKON FOR AGRICULTURE, 2022)
Sophisticated experimental technics and methods are exist, which are suitable to determine the toxin risk of different crops. As protection of susceptible varieties or hybrids are could not be solved by chemical and agronomical approaches, cultivation of crops with at least moderate resistance can be the solution. Several varieties and hybrids with this property are on the market. Differences in resistance between genotypes may be tenfold or more, so selection of more resistant lines substantially could improve the food and feed safety.
Keywords: cultivar registration; cereals; mycotoxin